Spatial Distribution of (R)-salbutamol in Rat Brain Following Nasal and Intravenous Administration Using DESI-MS - Rui Zhang; Jie Wu; Siyu Liu; LiangJun Deng; Junhua Hu; Xi Chen; Wen Tan (MDPI AG, 2020)
Recent studies have shown that β2-Adrenoreceptor is a regulator of the a-synuclein gene driving risk of Parkinson’s disease. The β2-AR agonist (R)-salbutamol, eutomer of rac-salbutamol, may hold therapeutic potential for Parkinson’s disease (PD) following nasal administration. In this study, we use desorption electrospray ionization mass spectrometry (DESI-MS) to analyze spatial distribution of (R)-salbutamol in rat brain following nasal and intravenous administration. Here, we report that (R)-salbutamol efficiently deliver to the brain and had more drug dosage exposure in rat’s brain through nasal route administration than that of intravenous route administration. In conclusion, administering (R)-salbutamol through nasal route of administration may hold advantages in improving spatial distribution and increased exposure of drug in brain.